2013
DOI: 10.5958/j.2319-5886.2.2.014
|View full text |Cite
|
Sign up to set email alerts
|

Anti diabetic effect of Momordica charantia (Bitter melone) on Alloxan induced diabetic rabbits

Abstract: Objective: to investigate the anti diabetic effect of the bitter melon on Alloxan induced diabetes in experimental animals (rabbits). Materials and Methods: the alcohol extract of whole fruit was tested for its efficacy in Alloxan (150mg/kg) induced diabetic rabbit. The diabetic rabbits were divided into 5groups. Group I (control) received 2% gumacasia, groupie (positive control) received standard drug Metformin (62.5mg+2%GA), group III, IV, V (T 1 T 2 T 3) were treated orally with a daily dose of 0.5(gm) 1gm,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
1
1
0
1
Order By: Relevance
“…The blood sugar levels are almost comes to the normal levels. The present results are agreed with Ying et al (2012); Yakaiah et al (2013) and Lin et al (2009) Yakaiah et al (2013 suggested that results of this study show that chronic oral administration of an extract of Momordica charantia fruit at an appropriate dosage may be good alternative anti diabetic agent in alloxan induced diabetics.…”
Section: Alloxan Induced Diabetes and Comparison With Bitter Melon Fruitsupporting
confidence: 93%
See 1 more Smart Citation
“…The blood sugar levels are almost comes to the normal levels. The present results are agreed with Ying et al (2012); Yakaiah et al (2013) and Lin et al (2009) Yakaiah et al (2013 suggested that results of this study show that chronic oral administration of an extract of Momordica charantia fruit at an appropriate dosage may be good alternative anti diabetic agent in alloxan induced diabetics.…”
Section: Alloxan Induced Diabetes and Comparison With Bitter Melon Fruitsupporting
confidence: 93%
“…The present results are agreed with other results. Sharma et al (2009); Yakaiah et al (2013); Puri and Prabhu (2002) suggested that alloxan treatment increased the blood glucose level in treated birds compared to the control rabbits. Alloxan induced experimental diabetes is also associated with marked reduction of anti-oxidant enzyme superoxide dismutase activity in islets cells.…”
Section: Alloxan Induced Diabetes and Comparison With Controlmentioning
confidence: 99%
“…Hal ini menunjukkan ekstrak buah pare memberikan efek penurunan kadar glukosa darah tergantung dosis. Ditunjukkan semakin tinggi dosis yang diberikan maka penurunan kadar glukosa darah semakin optimal (24).…”
Section: Hasil Dan Diskusiunclassified